Treatment of textile wastewater in a single-step moving bed-membrane bioreactor: Comparison with conventional membrane bioreactor in terms of performance and membrane fouling - Tecirli, Emine Sule; Akgun, Kadir; Caglak, Abdulkadir; Erkan, Hanife Sari; Engin, Guleda Onkal (WILEY, 2024)
Membrane bioreactor (MBR) is a promising technology for the treatment of municipal and industrial wastewater, including highly contaminated textile wastewater. However, membrane fouling remains a critical challenge due to reduced flux. This study investigates the efficacy of a moving bed MBR (MB-MBR) technology for textile wastewater treatment, focusing on chemical oxygen demand (COD) removal, and its impact on mitigating membrane fouling. In a 50-day study, a conventional MBR (R1) was compared with an MB-MBR (R2) augmented with free-floating biocarriers (accounting for 20% of the reactor volume). Both systems used flat sheet ceramic membrane modules. The results indicate that the MB-MBR achieved superior performance, with COD and colour removal of 89% and 81%, respectively, compared with 87% and 73% in the conventional MBR. Importantly, the introduction of biocarriers eliminated the need for offline physical membrane cleaning in the MB-MBR. The free-floating biocarriers lowered transmembrane pressure, reduced capillary suction time and reduced fouling through their scouring action. A conventional MBR and moving bed-MBR were compared in textile wastewater treatment. Almost equal COD removal efficiencies were found in both operations. Higher color removals were obtained by moving bed-MBR process. The moving bed-MBR reduced the TMP, CST of sludge and membrane fouling propensity.
Keywords: membrane fouling; moving-bed membrane bioreactor; textile wastewater; traditional membrane bioreactor; treatment performance; EXTRACELLULAR POLYMERIC SUBSTANCES; ACTIVATED-SLUDGE; REVERSE-OSMOSIS; BIO-CARRIERS; HYBRID; MITIGATION; ELECTROCOAGULATION; NANOFILTRATION; DEWATERABILITY; REMOVAL; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources